Quantification of Myocyte Disarray in Human Cardiac Tissue - Giardini, Francesco; Lazzeri, Erica; Vitale, Giulia; Ferrantini, Cecilia; Costantini, Irene; Pavone, Francesco S.; Poggesi, Corrado; Bocchi, Leonardo; Sacconi, Leonardo (Frontiers in Physiology, 2021)
Proper 3D-cardiomyocyte orientation is important for an effective tension production in cardiac muscle. Cardiac diseases can cause severe remodeling processes in the heart, such as cellular misalignment, that can affect both the electrical and mechanical functions of the organ. To date, a proven methodology to map and quantify myocytes disarray in massive samples is missing. Here, we present an experimental pipeline to reconstruct and analyze the three-dimensional cardiomyocyte architecture in massive samples. We employed tissue clearing, staining, and advanced microscopy techniques to detect sarcomeres in relatively large human myocardial strips with micrometric resolution. Z-bands periodicity was exploited in a frequency analysis approach to extract the 3D myofilament orientation, providing an orientation map used to characterize the tissue organization at different spatial scales. As proof-of-principle, we applied the proposed method to healthy and pathologically remodeled human cardiac tissue strips. Preliminary results suggest the reliability of the method, showing strips from a healthy donor are characterized by well-organized tissue, where the local disarray is log-normally distributed and slightly depends on the spatial scale of analysis; on the contrary, pathological strips shows pronounced tissue disorganization, characterized by local disarray significantly dependent on the spatial scale of analysis. A virtual sample generator is developed to link this multi-scale disarray analysis with the underlying cellular architecture. This approach allowed us for the first time to quantitatively assess tissue organization in terms of 3D myocyte angular dispersion, and may pave the way for developing novel predictive models based on structural data at cellular resolution.